Menghadapi Keberagaman: Strategi PAK di Masyarakat Majemuk - Sutarman Laia; Putri Sory; Emilia Wori Hana; Semuel Linggi Topayung (Berkat : Jurnal Pendidikan Agama dan Katolik, 2024)
Diversity in society is an unavoidable reality, especially in Indonesia which is known for its plurality of ethnicities, religions, and cultures. Christian Religious Education (PAK) has an important role in preparing the younger generation to live in harmony amidst differences. This article explores strategies that can be applied in PAK to face the challenges of diversity. The research conducted by the researcher is a qualitative descriptive study using a qualitative library approach. This approach focuses on describing the research problem. With an inclusive approach, PAK can help students understand and appreciate differences, promote interfaith dialogue, and encourage real actions that contribute to peace and social justice. The results show that PAK that is responsive to diversity is able to form individuals who not only have strong faith, but are also open and ready to contribute positively in a pluralistic society. The proposed strategies include integrating inclusive values ​​into the curriculum, developing interfaith dialogue skills, and strengthening student involvement in social activities that prioritize cooperation between religious communities. Christian Religious Education also plays an important role in improving the quality of Indonesian society, both in knowledge, attitudes, spirituality, and daily life. In this way, Indonesian people will have knowledge of God and strong faith in living a righteous life every day.